The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s00595-017-1504-z
|View full text |Cite
|
Sign up to set email alerts
|

Superiority of stapled side-to-side gastrojejunostomy over conventional hand-sewn end-to-side gastrojejunostomy for reducing the risk of primary delayed gastric emptying after subtotal stomach-preserving pancreaticoduodenectomy

Abstract: Background and purposeDelayed gastric emptying (DGE) is the most common complication following pancreaticoduodenectomy (PD). The clinical efficacy of stapled side-to-side anastomosis using a laparoscopic stapling device during alimentary reconstruction in PD is not well understood and its superiority over conventional hand-sewn end-to-side anastomosis remains controversial. The objective of this study was to evaluate the effectiveness of the stapled side-to-side anastomosis in preventing the development of DGE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
(50 reference statements)
3
7
2
Order By: Relevance
“…Previous researchers have reported that use of staplers for anastomosis does not increase postoperative complications in PD,67814171822 and we also observed this as well in the present study. The prevailing discipline notes that staple alimentary reconstruction is now widely used in upper and lower gastrointestinal tract surgery 323.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Previous researchers have reported that use of staplers for anastomosis does not increase postoperative complications in PD,67814171822 and we also observed this as well in the present study. The prevailing discipline notes that staple alimentary reconstruction is now widely used in upper and lower gastrointestinal tract surgery 323.…”
Section: Discussionsupporting
confidence: 91%
“…Other researchers have compared stapled anastomosis with hand-sewn anastomosis 61718. Sakamoto et al6 (2016) have reported that Roux-en-Y reconstruction using a stapler in PD was not inferior to the hand-sewn method in terms of incidence of DGE, and we found favorable results of stapled anastomosis for DJ in PPPD in terms of DGE incidence.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Regarding improvements in outcomes after PD, it should be noted that the median duration of hospital stay in this study was longer than that in most Western countries, although the results were almost compatible with hospital stay durations from other studies in Japan, which ranged from 18 to 39.5 days. 1,7,8,12,13,38 Differences in the health care insurance systems and medical expenses might influence postoperative care and patients behaviors, as discussed in other studies from Japan. 1,7,12,13 This study had several limitations.…”
Section: Discussionmentioning
confidence: 94%
“…In general, surgical procedures influenced DGE, indicating the superiority of pylorus resection, 7 antecolic gastrojejunostomy or duodenojejunostomy reconstruction, 8 Braun anastomosis, 9 Billroth II reconstruction 10,11 and side-to-side gastrojejunostomy. 12,13 However, recent studies including a meta-analysis reported conflicting findings, [2][3][4][14][15][16] resulting in a lack of evidencebased effective procedures that decrease DGE consistently. Few studies have focused on pharmacological treatment for DGE after PD.…”
Section: Introductionmentioning
confidence: 99%